Resonant x-ray scattering from the 4p quadrupole moment in YVO3 - Beale, T; Johnson, R; Joly, Y; Bland, SR; Hatton, P; Bouchenoire, L; Mazzoli, C; Prabhakaran, D; Boothroyd, A (2010)
We show that resonant scattering signals at the Bragg forbidden positions in YVO3 originate from the anisotropic nature of the atomic scattering factor. The E1-E1 scattering from the electric-quadrupole moment is explained entirely through the crystal structure and does not require sensitivity to 3d orbital order. Simulations of the resonance using the FDMNES code suggest that the Jahn-Teller distortion provides an insignificant contribution to the intensity of the forbidden reflection. Thus we show that resonant x-ray diffraction at the vanadium K -edge in YVO3 is largely insensitive, even indirectly, to 3d orbital order through Jahn-Teller distortions. © 2010 The American Physical Society.